The EU's increasingly complex finances: A ticking bomb? - Iain Begg (EconPol Forum, 2023)
The EU's finances have become more complex because of a proliferation of off‑budget mechanisms alongside the traditional budget. Most of these new mechanisms involve borrowing and lending activities. The agreement of the Next Generation EU response to the pandemic accentuates the trend towards off-budget mechanisms. It also means the EU has to borrow directly from financial markets to finance grants to member states, instead of using its own revenues. Increased resort to borrowing raises problems of legitimation, because the role of the European Parliament is more limited in relation to borrowing mechanisms than the powers it has over the annual budget and the multiannual financial framework. Servicing the EU's new borrowing and repaying the debt over the coming decades will place demands on future EU budgets. However, there is resistance to increasing the budget, while adopting new resources to fund it is politically challenging. For these reasons, there will be pressures to rethink the EU's finances and to focus more on EU-level public goods. Both will require bold decisions and efforts to over‑ come the bias towards the status quo of recent decades
Keywords: 330